Prevalensi Mukositis Oral pada Pasien Kanker Payudara yang Menerima Kemoterapi 5-Fluorouracil - trisna ajani, anggra; Milya Novera; Fiola Finomia Honesty; Putri Minas Sari; Debby Shinthania; Mariza Elvira; Espasari; Yeni Masbiran; Keken Erva Nanda; Shindy Gustarina (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2025)
Cancer treatment is currently carried out in various ways according to the stage of cancer diagnosed by the doctor. One of the cancer treatments is combination chemotherapy. Chemotherapy given to breast cancer patients is 5-fluorouracil combination chemotherapy, which can damage the basal epithelial cell layer directly, causing death of clonogenic cells, mucosal atrophy and ulceration called oral mucositis. Oral mucositis will be influenced by various things, namely high doses, age, gender, type of chemotherapy drug, repeated chemotherapy schedules (chemotherapy cycles), poor nutritional status, plus oral hygiene conditions. The purpose of this study was to determine the frequency distribution of oral mucositis characteristics of breast cancer patients with 5-fluorouracil combination chemotherapy. The research method is descriptive with consecutive sampling. The sample obtained was 45 people. The results of the study showed that the frequency distribution with the most age characteristics in the early elderly, almost all were diagnosed with stage, less than half underwent the 5th chemotherapy cycle and more than half had normal nutritional status, and more than half of breast cancer patients with 5-fluorouracil combination chemotherapy with mild oral mucositis. The suggestion of this study is that nurses in the chemotherapy room can provide education on the management of oral mucositis with nursing modalities such as cryotherapy